Unusual scaling laws for plasmonic nanolasers beyond the diffraction limit - Suo Wang (Nature Portfolio, 2017)
Since the first proposal for plasmonic nanolasers there has been a debate about the limitations on performance posed by the inherent losses in metallic systems. Here, the authors compare over 100 plasmonic and photonic laser devices and find sub-wavelength plasmonic lasers to be advantageous.